Keteramatan Sistem Deskriptor Kontinu - Muhammad Wakhid Musthofa; Ari Suparwanto (Jurnal Fourier, 2012)
In this paper the observability of continuous descriptor system of the form Ex(t)= Ax(t) Bu(t), x(0)=x0 will be studied, where E,A, and B are constant matrices that may be singular and u(t) is piecewise continuous function which is differentiated (m-1) times, where m is the degree of nilpotency system. Two definitions about observability of descriptor systems along with their characterizations given by Dai and Yip will be both discussed, then further the relationship and comparison between these characterizations will be presented.